System of Inheritance as a Preservation Effort of Kuriding In South Kalimantan - Muhammad Najamudin; Wadiyo Wadiyo; Syahrul Syah Sinaga (Universitas Negeri Surabaya, 2023)
This research generally aims to look at the inheritance system as an effort to preserve kuriding music in South Kalimantan. The method used is a qualitative method with an ethnomusicological approach, namely kuriding instrument craftsmen, academics, and the community in South Kalimantan. The main data collection tool in this study is the researcher himself as the key instrument. Based on the results of research on inheritance systems (1) History, (2) Concept of Inheritance, (3) Performance Presentation, (4) How to Play, and (5) Conservative Ideological Values. The research is expected to provide knowledge about South Kalimantan kuriding music to the community as the owner of the art.